Effectiveness of teenage parenthood package on maternal and fetal outcomes: a mixed-method pilot study - Elizebeth Rani V; Jolly Ranjith; T Amutha; S Kanchana; D Celina (Universitas Airlangga, 2026)
ABSTRACTIntroduction: Teenage pregnancy poses significant maternal and neonatal health risks, often compounded by delayed antenatal care, inadequate nutrition, and limited knowledge. Promoting healthy practices such as regular antenatal attendance, balanced nutrition, hygiene, adequate rest, exercise, and self-care is vital to improving pregnancy outcomes among adolescents. This pilot study evaluated the effectiveness of a Teenage Parenthood Package (TPP) on maternal and fetal outcomes and explored the lived experiences of teenage mothersMethods: A mixed-method design with an explanatory sequential approach was adopted. In Phase I, a quasi-experimental study was conducted among 30 teenage mothers (15 experimental, 15 control) selected through purposive sampling at the Institute of Obstetrics and Gynecology, Chennai. The Teenage Parenthood Package—comprising trimester-based antenatal education, BMI-specific dietary counseling, exercise demonstrations, and psychosocial guidance—was administered to the experimental group. Quantitative data were analyzed using paired and independent t-tests, Pearson’s correlation, and chi-square tests. Phase II involved qualitative exploration using in-depth interviews analyzed through Colaizzi’s method.Results: The Teenage Parenthood Package significantly improved knowledge, dietary practices, and labor outcomes among teenage mothers. Although maternal–fetal attachment showed no significant difference between groups, qualitative findings revealed challenges including stigma, lack of familial support, and postpartum emotional distress. Integration of both data sets emphasized the value of structured, nurse-led interventions.Conclusion: The Teenage Parenthood Package effectively enhanced maternal knowledge, dietary practices, and labor outcomes, underscoring the importance of comprehensive, adolescent-centered interventions to improve maternal and fetal health outcomes and psychosocial well-being.Keywords: teenage mothers, maternal outcome, fetal outcome, experience of pregnancy, teenage parenthood package